90=-6+8(p+4)

Simple and best practice solution for 90=-6+8(p+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90=-6+8(p+4) equation:


Simplifying
90 = -6 + 8(p + 4)

Reorder the terms:
90 = -6 + 8(4 + p)
90 = -6 + (4 * 8 + p * 8)
90 = -6 + (32 + 8p)

Combine like terms: -6 + 32 = 26
90 = 26 + 8p

Solving
90 = 26 + 8p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-8p' to each side of the equation.
90 + -8p = 26 + 8p + -8p

Combine like terms: 8p + -8p = 0
90 + -8p = 26 + 0
90 + -8p = 26

Add '-90' to each side of the equation.
90 + -90 + -8p = 26 + -90

Combine like terms: 90 + -90 = 0
0 + -8p = 26 + -90
-8p = 26 + -90

Combine like terms: 26 + -90 = -64
-8p = -64

Divide each side by '-8'.
p = 8

Simplifying
p = 8

See similar equations:

| (5n^2-n+6)+(8n^2-11)=0 | | 6+3=8x+4 | | -36+y=-2 | | -6(6x+8)=-36+48 | | 14y=350 | | 12x+13=115 | | 15y/12y^5 | | 0.3x-1=0.32 | | 5x*3-8+2x-4=2+3x*6 | | 120/10=-3y | | -12=-2.5x-3 | | 4-x+8=6 | | 2x+2x+3=-7 | | 0.5x+0.16=0.75 | | 6k^2-53k-9=0 | | 4x*6=8x-1 | | 4(x+9)=-24 | | 0.5x+6=0.75 | | -30=9/-5 | | 2-2n=3n+10 | | 4d-3=d+42 | | 5(N+1)=-2n+4(n-4) | | X-7+20=7x-10 | | -2/5÷-2/3 | | (3z+7)(3z+7)= | | 3x=.5(5x+12) | | y+5=-5x | | x^2+31=24 | | D+(1.1+-5d)=4.8 | | 12(5-x)=8 | | (2m-3)=20-4m | | 6(b-5)=18-2b |

Equations solver categories